A Strategy for Synthesis of Carbon Nitride Induced Chemically Doped 2D MXene for High‐Performance Supercapacitor Electrodes. Issue 15 (30th January 2018) - Yoon, Yeoheung; Lee, Minhe; Kim, Seong Ku; Bae, Garam; Song, Wooseok; Myung, Sung; Lim, Jongsun; Lee, Sun Sook; Zyung, Taehyoung; An, Ki‐Seok
Abstract: A step‐by‐step strategy is reported for improving capacitance of supercapacitor electrodes by synthesizing nitrogen‐doped 2D Ti2 CT x induced by polymeric carbon nitride (p‐C3 N4 ), which simultaneously acts as a nitrogen source and intercalant. The NH2 CN (cyanamide) can form p‐C3 N4 on the surface of Ti2 CT x nanosheets by a condensation reaction at 500–700 °C. The p‐C3 N4 and Ti2 CT x complexes are then heat‐treated to obtain nitrogen‐doped Ti2 CT x nanosheets. The triazine‐based p‐C3 N4 decomposes above 700 °C; thus, the nitrogen species can be surely doped into the internal carbon layer and/or defect site of Ti2 CT x nanosheets at 900 °C. The extended interlayer distance and c ‐lattice parameters ( c ‐LPs of 28.66 Å) of Ti2 CT x prove that the p‐C3 N4 grown between layers delaminate the nanosheets of Ti2 CT x during the doping process. Moreover, 15.48% nitrogen doping in Ti2 CT x improves the electrochemical performance and energy storage ability. Due to the synergetic effect of delaminated structures and heteroatom compositions, N‐doped Ti2 CT x shows excellent characteristics as an electrochemical capacitor electrode, such as perfectly rectangular cyclic voltammetry results (CVs, R 2 = 0.9999), high capacitance (327 F g −1 at 1 A g −1, increased by ≈140% over pristine‐Ti2 CT x ), and stable long cyclic performance (96.2% capacitance retention after 5000 cycles) at high current density (5 A g −1 ). Abstract : Carbon nitride ( p ‐C3 N4 ) induced chemically nitrogen doped 2D Ti2 CT x for supercapacitor electrodes is reported. The synthesized 900N‐Ti2 CT x exhibits a high N atom concentration of 15.48% via thermal decomposition process of p‐C3 N4, and significant improvements in supercapacitor performance parameters, such as capacitance, rate, and cyclic life, are achieved due to the delaminated structures, high nitrogen content, and improved electrical conductivity.